2019
DOI: 10.4103/ams.ams_159_17
|View full text |Cite
|
Sign up to set email alerts
|

KIMURA'S disease – An E[X]clusive condition

Abstract: Kimura's disease is a rare autoimmune disease of unrecognized etiology. Due to its unspecific clinical presentation and laboratory studies, Kimura's is a diagnosis of exclusion . A systematic multidisciplinary approach is mandatory to rule out the other common causes of cervicofacial lymphadenopathy. A thorough Histopathological examination including immunohistochemical analysis along with the presence of specific biochemical markers, including raised Absolute eosinophilic count is necessary to conclude the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…3,6 Kimura disease affects mostly Asian males with a median age of 32 years, and male-to-female ratio is about 5:3. 3,6 Various symptoms may occur in KD patients. In a review of 22 patients of KD, Kottler et al 7 indicated a history of pruritus or atopic diathesis in 40% of patients, whereas 58% of patients had atopic dermatitis or lichen simplex chronicus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,6 Kimura disease affects mostly Asian males with a median age of 32 years, and male-to-female ratio is about 5:3. 3,6 Various symptoms may occur in KD patients. In a review of 22 patients of KD, Kottler et al 7 indicated a history of pruritus or atopic diathesis in 40% of patients, whereas 58% of patients had atopic dermatitis or lichen simplex chronicus.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic reaction, infection, and autoimmune reactions may play a role in the pathogenesis. 6 Eosinophilia (up to 10%-20% eosinophils and increased leucocytes) and increased serum IgE levels are characteristic. 9 Elevated IgE, tumor necrosis factor-α, interleukin (IL)-4, IL-5, IL-13, and mast cell levels are noted in blood and lesion tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conspicuous features of Kimura's disease on histopathology include hyperplastic lymphoid follicles with prominent germinal centers and eosinophilic infiltration. Laboratory tests show that eosinophils on routine blood testing and IgE in serum are significantly increased in patients with Kimura's disease (6)(7)(8)(9)(10)(11). Sometimes, Kimura's disease can occur in other organs, especially the kidneys, where it takes the form of membranoproliferative glomerulonephritis (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…The histological picture with the formation of lymphoid follicles and intense aggregates of eosinophils (which sometimes form micro abscesses), vascular proliferation, and fibrosis are highly suggestive of KD. 12,13 Differential diagnosis of KD would include angiolymphoid hyperplasia with eosinophilia (ALHE), Kikuchi disease, Mikulicz's disease, and most importantly Hodgkin and non-Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%